The Perspective of Bureaucratic Reform (Kang Yoto's Leadership) in Bojonegoro - Aziz, Fadian Nur; Roziqin, Ali (Departemen Ilmu Administrasi FISIP UNHAS, 2020)
The short article aims to discuss the bureaucratic reform by Kang Yoto during his leadership in Bojonegoro Regency. In the governance structure, the local government is a street level bureaucracy that must be responsive to community development. Using library analysis and focus group discussions, Authors also discuss with Kang Yoto as directly, when the process of entoring at the University of Muhammadiyah Malang. Authors analyze the bureaucratic reform movement carried out by Kang Yoto able to change people's stigma better towards bureaucracy. Some of the things done by Kang Yoto such as the bloated Friday, transforming public services and bureaucratic innovation succeeded in bringing a positive impact on development in Bojonegoro Regency. Needing this shows the success of bureaucratic reform in the regions needs strong commitment and leadership in the regions. This paper is expected to be able to provoke potential regional leaders who will fight in the simultaneous Regional Election in 2020.